The Influence of Summative Evaluation on Pupils' Dropout in Primary Schools in Rubaare Town Council Ntungamo District. - Mwogyera, Godfrey (Kabale University, 2024)
The study focused on the influence of summative evaluation on pupils' dropout in primary schools in Rubaare town council, Ntungamo district. The objectives of the study were to identify factors leading to pupil dropout in School, to find out the impact of summative evaluation on pupils' dropout in primary schools, and to identify pupils' perceptions of the Classroom summative evaluation Environment. There was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on summative evaluation as an independent variable and pupils dropping out as the dependent variable. Research used descriptive research design and methods of data collection were put into action. The research used both qualitative and quantitative methods of data collection and analysis. The research used simple random sampling techniques in collecting and analyzing data and was used to provide equal chances to the sample size. Purposive sampling was also used to collect data from respondents who participated in the study. The study findings indicate that there were factors leading to pupils dropping out of school including; school factors, teacher-pupil relationship, teaching approaches, distance from school, school curriculum, corporal punishments, and school management style. However, the majority of the respondents revealed that school factors 20% were the major factor leading to pupils dropping out. Findings on the impacts of summative evaluation on pupils dropping out of primary schools include; the development of pupils' understanding increased performance, accountability for stakeholders, easy analysis of academic performance, engages pupils in class, and increased pupils' academic morale. The majority of the respondents revealed that an increase in performance of 23% was the major impact of summative evaluation on pupils dropping out and pupils' perceptions of the classroom summative environment include; self-reliance, more teaching practices by teachers, pupils' anxiety, stakeholder concern, and teacher immediate response. The majority of the respondents revealed more teaching practices by teachers with 20% of the pupils' perceptions of the classroom summative environment. Recommendations for the study include that there is a need to invite more teacher-oriented and professional head teachers to talk about summative evaluation in primary school.